Job-Related and Nonjob-Related Gossips Among Low-Ranked Employees in Unionized Service Organization - Bashir, Mohsin; Shabbir, Rizwan; Saleem, Sharjeel; Abrar, Muhammad; Saqib, Shahnawaz; Gill, Shahzad Habib (Frontiers in Psychology, 2020)
Workplace incivility is a common phenomenon that is frequently found across all organizations and cultures. This study was planned to investigate the impact of workplace incivility on job-related gossips and non-job related gossips through the mediating role of cynicism and psychological contract violation. The perspective of low-ranked unionized employees was explored using the survey method. The population of this study was low-ranked employees working in the largest power distribution company of Pakistan, serving across thirteen districts. Under the domain of probability sampling, stratified sampling was applied, and eight strata were considered to collect data on the basis of the geographical distribution of consumers. A total of four hundred questionnaires were distributed among the employees of eight circles, 50 from each. Three hundred forty questionnaires were received back, out of which 301 were completely filled, which were considered for analysis. SmartPLS 3.2.7 was used to analyze the data through structural equation modeling. From theoretical perspective this study has made several contributions by investigating the impact of workplace incivility in South Asian context and documenting the impact of incivility from the perspective of individuals belonging to minority socio-cultural status. Besides supporting existing literature, this study provided a unique argument that low-ranked employees in South Asian societies don’t spread non-job related gossips. This finding is contradictory to the existing literature; and, thus, calls for future research to identify this inconsistency. Limitations and future directions are also discussed.